EFEKTIFITAS DAN EFISIENSI YOUTUBE SEBAGAI MEDIA PUBLIKASI: Study pada Video ASSA Tour Keliling Jawa 2 - Yan Haryadie; Muhammad Nur Kholis AR (Melati Institute, 2022)
Based on Law Number 14 of 2008 concerning the disclosure of public information, every social activity that involves many people or the public is required to provide information needed by the public in order to create transparent and accountable information. ASSA Tour Keliling Jawa 2Anyer – Panarukan 2727 Km was colored by program innovations that attracted the attention of the public, one of which was the use of new media to communicate with the public through YouTube as a means of communication transparency. The purpose of this study was to determine the effectiveness and efficiency of using YouTube on ASSA videos. ASSA Tour Keliling Jawa 2 in disseminating information is also to find out the obstacles faced by ASSA Tour Keliling Jawa 2 in disseminating information via youtube. This research method uses descriptive analysis method, which describes all the data obtained both from interviews and observations of researchers. The next step, after the data was obtained through interviews, the researchers analyzed the data with the existing conceptual, then processed and entered into certain parts. The results of this study are expected to have cognitive, affective, personal integration, social integration, and fantasizing effects. These effects are to determine the effectiveness and efficiency of using YouTube as a publication medium for the ASSA Tour Keliling Jawa 2 video.